Public-private competition in regulated markets - Ghandour, Ziad (2019)
We analyse the eﬀect of competition on quality provision in mixed markets, such as healthcare and education, where public and private providers coexist. We draw two key assumptions about the public provider in such markets, namely in that it faces a regulated price and is (partly) motivated. We also explore the eﬀects of changes in the state subsidy and co-payment fees. Our main contribution is that, under certain circumstances, more competition leads to lower average quality in equilibrium. Similarly, the eﬀects of higher co-payment fees or larger state subsidies on average quality are also a priori ambiguous. These conclusions hold regardless of whether providers seek proﬁt maximisation or the public provider has altruistic preferences. Furthermore, we characterise the incentives for the private provider to unilaterally relocate towards the public provider.